EFFECT OF CONVECTIVE SYSTEM EVENTS IN THE WEST JAVA REGION WITH ESTIMATED VALUE OF AREA REDUCTION FACTOR (ARF) (CASE STUDY: WEST JAVA REGION) - Saefulloh
ARF is a ratio value of area rainfall to resolve limitation of spatial rainfall data. Spatially in various areas of a watershed have different ARF values. Rainfall characteristics in a watershed need to be known in calculating the ARF value and the formation of rainfall in a watershed is influenced by the regional convective system. So that the convective system of a region affects the ARF value. In this study, the ARF was performed to determine the ratio of rainfall depth spatially in various areas with a certain duration using the Global Precipitation Measurement (GPM) Final Precipitation data. The ARF analysis was divided into 2 regions i.e based on the frequency of the convective system events for East Priangan area and non-East Priangan area. The results showed that East Priangan area has a higher ARF curve for rain with duration ? 12 hours because the East Priangan area has a high frequency of Mesoscale Convective System (MCS) events for the PECS type so that for spatially the rainfall has evenly distributed. Meanwhile, for rain with duration > 12 hours, Bantxen area has a higher ARF curve due to the convective system for rain with duration > 12 hours which mostly occurs in marine areas. The ARF curve has influenced by the life phase of the convective system in area.